2018
DOI: 10.1177/1369433218796411
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on seismic behavior of precast hybrid steel–concrete beam

Abstract: This study aims to investigate the seismic behavior of precast hybrid steel-concrete beams. Five full-scale beam specimens, including four precast hybrid steel-concrete beams and a conventional precast concrete beam, were tested under cyclic loading. Furthermore, a new connection form was proposed to facilitate the constructability of the steel-to-concrete connection. The main experimental parameters were the steel beam length and the longitudinal reinforcement ratio. In addition, the influence of the reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The above results were consistent with the failure modes observed during the test, the use of smaller spacing of stirrups reduced damage to the plastic hinge region, thus enhancing the inelastic deformability. In general, for CFPHCCT1–7, the μ values gained in the test were ranged from 3.77 to 5.97, which achieved the demand of μ ≥ 3.0 for concrete members (Zhang et al, 2018b). Furthermore, based on the classification of ductility levels (Morrison et al, 2012), CFPHCCT columns have moderate (3.0 ≤ μ < 4.0) to high ( μ ≥ 4.0) levels of ductility.…”
Section: Test Results and Discussionmentioning
confidence: 94%
“…The above results were consistent with the failure modes observed during the test, the use of smaller spacing of stirrups reduced damage to the plastic hinge region, thus enhancing the inelastic deformability. In general, for CFPHCCT1–7, the μ values gained in the test were ranged from 3.77 to 5.97, which achieved the demand of μ ≥ 3.0 for concrete members (Zhang et al, 2018b). Furthermore, based on the classification of ductility levels (Morrison et al, 2012), CFPHCCT columns have moderate (3.0 ≤ μ < 4.0) to high ( μ ≥ 4.0) levels of ductility.…”
Section: Test Results and Discussionmentioning
confidence: 94%
“…Qin carried out research on the optimal position of the steel-concrete joint section of the hybrid girder bridge through a parametric sensitivity analysis [19]. Zhang proposed a new type of connection form to facilitate the constructability of the steel-to-concrete connection and confirmed its good seismic behavior in precast hybrid steel-concrete girders [20]. He deduced a relationship between the optimal length of the steel-concrete connection and the length ratio of side span to main span [21], which was proved to be an efficient method for the preliminary design of hybrid girder bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Through on-site tests and numerical analysis, Li et al [23] evaluated the dynamic performance of a steel-concrete hybrid beam bridge with spread steel box beam under vehicle loads, and the results showed that the maximum impact coefficient of the bridge met the Chinese and American bridge design codes. Zhang et al [24] conducted an experimental study on hybrid beams from the perspective of seismic resistance and found that the failure mode of precast hybrid beams was different from that of precast concrete beams. Lu et al [25] carried out a finite element analysis on the fatigue performance of an important component of the joint, shear connectors.…”
Section: Introductionmentioning
confidence: 99%